ANALISA BAHAN BAKAR SERABUT DAN CANGKANG PADA KATER UAP KAPASISTAS 20 TON/JAM DI PT. BEURATA SUBUR PERSADA - Mirza Fazillah ma; Al Munawir; Joli Supardi; Muzakir Muzakir (universitas teuku umar, 2021)
Limited Liability Company (PT) Beurata Subur Persada is a large company engaged in palm oil processing with an area of approximately 23 hectares of activity. In the processing there is a steam catter/boiler working tool. This steam boiler engine is often used as a production engine in industrial companies. Steam boiler or boiler is a container that is very tightly closed in which the heat of combustion flows until hot steam is formed. The analysis uses a data processing application, then the calculation and data retrieval starts from march 11 to August 13 2021. The results of the study state that the components of the steam boiler at a capacity of 20 Tons/hour are the most important, namely the burner, evaporator pipe, combustion chamber, water reservoir. from economizers, superheaters, steam heaters and ash or ash collection devices from combustion. Calculations at a high calorific value (HHV) of 5,691.17 Kcal/Kg and a low calorific value (LHV) of 4,608.96 Kcal/Kg used shell and fiber fuel with a ratio of 3:1 with a percentage of 25% shell and 75% fiber. Keywords: Steam Boiler,Heat Value, PT. Beurata Subur Persada